High-temperature creep properties of 9Cr-ODS tempered martensitic steel and quantitative correlation with its nanometer-scale structure. Issue 3 (4th March 2023) - Ohtsuka, Satoshi; Shizukawa, Yuta; Tanno, Takashi; Imagawa, Yuya; Hashidate, Ryuta; Yano, Yasuhide; Onizawa, Takashi; Kaito, Takeji; Ohnuma, Masato; Mitsuhara, Masatoshi; Nakashima, Hideharu
ABSTRACT: The Japan Atomic Energy Agency (JAEA) has been developing 9Cr-oxide dispersion strengthened (ODS) tempered martensitic steel (TMS) as a candidate material for use in the fuel cladding tubes of sodium-cooled fast reactors (SFRs). The creep property is essential for the fuel cladding tube of SFR; the reliable prediction of in-reactor creep-rupture strength is critical for implementing the 9Cr-ODS TMS cladding tube in the SFR. This study investigated the quantitative correlation between the creep properties of 9Cr-ODS TMS at 700°C and the dispersions of nanosized oxides by analyzing the creep data and the material's nanostructure. The possibility of deriving a formula for estimating the in-reactor creep properties of 9Cr-ODS TMSs based on an analysis of the nanostructure of neutron-irradiated 9Cr-ODS TMSs was also discussed. The creep properties of 9Cr-ODS TMS at 700°C closely correlated with the dispersion of nanosized oxide particles. The correlation between creep-rupture lives and nanosized oxide particle dispersion in 9Cr-ODS TMS was determined using existing creep models. The elucidation of correlation between the stress exponent of secondary creep rate and the nanostructure is essential to enhance future modeling reliability and formulation. Graphical Abstract: uf0001